1980
DOI: 10.1083/jcb.84.2.404
|View full text |Cite
|
Sign up to set email alerts
|

On the entry of semliki forest virus into BHK-21 cells

Abstract: The pathway by which Semliki Forest virus (SFV), a membrane-containing animal virus, enters BHK-21 cells was studied morphologically and biochemically . After attaching to the cell surface, the majority of viruses was rapidly trapped into coated pits, internalized by endocytosis in coated vesicles, and sequestered into intracellular vacuoles and lysosomes . Direct penetration of viruses through the plasma membrane was never observed .To assess the possible involvement of lysosomes in the release of the genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
544
1
4

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 762 publications
(576 citation statements)
references
References 49 publications
27
544
1
4
Order By: Relevance
“…Since infection in this calf had already progressed to the large intestine, it is probable that a second wave of infection had begun and cells of the mid-jejunum were newly infected, lacking mature, assembled virions but possessing viral antigen, nonetheless. The presence of Breda virions in close association with tips and sides of microvilli and within coated pits suggests that the virus may enter cells by receptor-mediated endocytosis (RME), a common mechanism of virus uptake (Goldstein et al, 1979;Helenius et al, 1980). This is supported further by the restricted association of virus with microvilli of absorptive enterocytes only.…”
Section: Discussionmentioning
confidence: 62%
“…Since infection in this calf had already progressed to the large intestine, it is probable that a second wave of infection had begun and cells of the mid-jejunum were newly infected, lacking mature, assembled virions but possessing viral antigen, nonetheless. The presence of Breda virions in close association with tips and sides of microvilli and within coated pits suggests that the virus may enter cells by receptor-mediated endocytosis (RME), a common mechanism of virus uptake (Goldstein et al, 1979;Helenius et al, 1980). This is supported further by the restricted association of virus with microvilli of absorptive enterocytes only.…”
Section: Discussionmentioning
confidence: 62%
“…Others have also observed the endocytosis of probes and liga~ds into vacuoles morphologically similar to those described here (12,45,48). In particular Van Deurs et al (42) reported that cationized ferritin initially entered electronlucent endocytic vacuoles and "light" multivesicular bodies containing some vesicular profiles, and only later could been seen in "dark" multivesicular bodies and dense bodies.…”
Section: Endocytosismentioning
confidence: 85%
“…3, a and a') the fluorescence appeared mainly as dots at the apical surface. This is the pattern generally seen when viruses are added to MDCK cells (22) or to BHK cells (12), and probably represents viruses bound or fused mainly to microvilli on the Fig. 3 were incubated at 31 °C after implantation and EDTA treatment at 0°C and then processed for differential immunofluorescence staining as described in Fig.…”
Section: Redistribution Of Implanted G Protein: Observations By Immunmentioning
confidence: 99%
“…Our previous studies on virus entry and uncoating have shown that incoming viruses receive signals from the host cell that trigger appropriate molecular changes in structural proteins required for penetration and uncoating (Helenius et al, 1980;Helenius, 1992). For example, independent signals for membrane fusion and for uncoating of influenza virus are mediated by the low pH in endosomes (Martin and Helenius, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…These processes are rather well understood for several enveloped animal viruses that use refined strategies of membrane fusion and uncoating (for reviews see Helenius, 1992;Kielian and Jungerwirth, 1990;Marsh and Helenius, 1989). Some penetrate directly through the plasma membrane while others enter from endosomes (Helenius et al, 1980;Pauza, 1991;Rigaut et al, 1991;Wittels and Spear, 1991). For nonenveloped viruses, the early events in the replication cycle are far less understood.…”
Section: Introductionmentioning
confidence: 99%